Low-weight polyethylenimine cross-linked 2-hydroxypopyl-ß-cyclodextrin and folic acid as an efficient and nontoxic siRNA carrier for gene silencing and tumor inhibition by VEGF siRNA - Li JM (Dove Medical Press, 2013)
Jin-Ming Li, Yuan-Yuan Wang, Wei Zhang, Hua Su, Liang-Nian Ji, Zong-Wan Mao MOE Key Laboratory of Bioinorganic and Synthetic Chemistry, School of Chemistry and Chemical Engineering, Sun Yat-sen University, Guangzhou, People's Republic of China Background: Targeted delivery of small interfering RNA (siRNA) has been regarded as one of the most important technologies for the development of siRNA therapeutics. However, the need for safe and efficient delivery systems is a barrier to further development of RNA interference therapeutics. In this work, a nontoxic and efficient siRNA carrier delivery system of low molecular weight polyethyleneimine (PEI-600 Da) cross-linked with 2-hydroxypopyl-β-cyclodextrin (HP-β-CD) and folic acid (FA) was synthesized for biomedical application. Methods: The siRNA carrier was prepared using a simple method and characterized by nuclear magnetic resonance and Fourier transform infrared spectroscopy. The siRNA carrier nanoparticles were characterized in terms of morphology, size and zeta potential, stability, efficiency of delivery, and gene silencing efficiency in vitro and in vivo. Results: The siRNA carrier was synthesized successfully. It showed good siRNA binding capacity and ability to protect siRNA. Further, the toxicity of the carrier measured in vitro and in vivo appeared to be negligible, probably because of degradation of the low molecular weight PEI and HP-β-CD in the cytosol. Flow cytometry and confocal microscopy confirmed that the FA receptor-mediated endocytosis of the FA-HP-β-CD-PEI/siRNA complexes was greater than that of the HP-β-CD-PEI/siRNA complexes in FA receptor-enriched HeLa cells. The FA-HP-β-CD-PEI/siRNA complexes also demonstrated excellent gene silencing efficiency in vitro (in the range of 90%), and reduced vascular endothelial growth factor (VEGF) protein expression in the presence of 20% serum. FA-HP-β-CD-PEI/siRNA complexes administered via tail vein injection resulted in marked inhibition of tumor growth and reduced VEGF protein expression in the tumors. Conclusion: Our results suggest that the FA-HP-β-CD-PEI complex is a nontoxic and highly efficient gene carrier with the potential to deliver siRNA for cancer gene therapy effectively in vitro and in vivo. Keywords: polyethyleneimine, 2-hydroxypropyl-β-cyclodextrin, folic acid, siRNA carrier, vascular endothelial growth factor, gene silencing